Pengaruh Word Of Mouth Dan Kualitas Produk Terhadap Minat Beli Produk Sotong UMKM Tamisari Tasikmalaya - Amirah Makarim, Siti; Haryati, Sani (Shofanah Media Berkah, 2023)
This study was conducted with the aim of investigating the impact of word of mouth (WOM) and product quality on the purchasing interest of squid products produced by Tamisari's Micro, Small, and Medium Enterprises (UMKM) in Tasikmalaya. The research method employed a quantitative descriptive approach, with data analysis techniques using Multiple Regression Analysis. The study population encompassed all consumers of Tamisari's squid products, and due to the unknown population size, the Accidental Sampling technique was employed with a sample size of 63, determined based on the Cochran formula. The results of this study indicate that, partially, word of mouth and product quality significantly influence the purchasing interest in Tamisari's squid products. This is supported by the significance values of 0.005 < 0.05 for word of mouth and 0.017 < 0.05 for product quality. Simultaneously, word of mouth and product quality also have a significant influence on the purchasing interest in Tamisari's squid products, with a significance value of 0.001 < 0.05. The overall impact of word of mouth and product quality on the purchasing interest in Tamisari's squid products is 23.2%, while the remaining 76.8% is influenced by variables or other factors not included in this study.